Exploring Prospective Teachers’ Conceptions in Thermal Physics - Namrata (Voices of Teachers and Teacher Educators, 2024)
A substantial body of research has documented the prevalence of naïve understandings of scientific concepts among students. These misconceptions can impede learning and persist despite classroom instruction. This study examined the understanding of fundamental thermal concepts, such as heat transfer, specific heat, the relationship between boiling point and pressure, and phase changes, among 170 prospective teachers from various colleges. The data revealed that a significant number of participants held conceptions that deviated from established scientific principles. Additionally, the study identified a variety of reasoning employed by prospective teachers to explain these concepts. Building on these findings, the researcher developed a range of strategies to address the identified alternative conceptions.